Metal-support interaction boosts the stability of Ni-based electrocatalysts for alkaline hydrogen oxidation - Xiaoyu Tian; Renjie Ren; Fengyuan Wei; Jiajing Pei; Zhongbin Zhuang; Lin Zhuang; Wenchao Sheng (Nature Communications, 2024)
Abstract Ni-based hydrogen oxidation reaction (HOR) electrocatalysts are promising anode materials for the anion exchange membrane fuel cells (AEMFCs), but their application is hindered by their inherent instability for practical operations. Here, we report a TiO2 supported Ni4Mo (Ni4Mo/TiO2) catalyst that can effectively catalyze HOR in alkaline electrolyte with a mass activity of 10.1 ± 0.9 A g−1 Ni and remain active even up to 1.2 V. The Ni4Mo/TiO2 anode AEMFC delivers a peak power density of 520 mW cm−2 and durability at 400 mA cm−2 for nearly 100 h. The origin for the enhanced activity and stability is attributed to the down-shifted d band center, caused by the efficient charge transfer from TiO2 to Ni. The modulated electronic structure weakens the binding strength of oxygen species, rendering a high stability. The Ni4Mo/TiO2 has achieved greatly improved stability both in half cell and single AEMFC tests, and made a step forward for feasibility of efficient and durable AEMFCs.